Holocene Interactions Between Glacier Retreat, Sea Ice Formation, and Atlantic Water Advection at the Inner Northeast Greenland Continental Shelf - Syring, Nicole; Lloyd, Jeremy M.; Stein, Ruediger; Fahl, Kirsten; Roberts, Dave H.; Callard, Louise; O'Cofaigh, Colm; 2 Department of Geography Durham University Durham UK; 1 Alfred Wegener Institute (AWI) Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; 4 School of Geography, Politics and Sociology Newcastle University Newcastle upon Tyne UK (Paleoceanography and Paleoclimatology, 2020)
During the past four decades significant decrease in Arctic sea ice and a dramatic ice mass loss of the Greenland Ice Sheet (GIS) has been coincident with global warming and an increase in atmospheric CO2. In Northeast Greenland significant mass loss from the outlet glaciers Nioghalvfjerdsbræ (79NG) and Zachariæ Isstrøm (ZI) and intensive seasonal breakup of the local Norske Øer Ice Barrier (NØIB) have also been observed since 2000. In order to better understand the processes driving these modern changes, studies of paleoclimate records are important and of major societal relevance. A multiproxy study including organic‐biogeochemical and micropaleontological proxies was carried out on a marine sediment core recovered directly in front of 79NG. Data from Core PS100/270 evidenced a strong inflow of warm recirculating Atlantic Water across the Northeast Greenland shelf from the early Holocene between ~10 and 7.5 ka. An overall high in phytoplankton productivity occurred within a stable sea ice margin regime, accompanied by 79NG retreat most probably triggered by peak solar insolation and changes in the local ocean circulation. Enhanced basal melt of the underside of 79NG at ~7.5 ka then led to the total disintegration of the ice shelf. The released freshwater would have driven water column stratification and promoted the formation of the local landfast ice barrier, which is shown by lowered biomarker values and foraminifera abundances toward the end of the early Holocene. Near perennial sea ice conditions with short summers and 79NG retreat to the inner fjord then prevailed from ~7.5 to ~0.8 ka. Key Points: Multiproxy record allowed reconstruction of NEG ice sheet retreat and sea ice history from the last deglaciation to the late Holocene. Increased inflow of warm recirculating Atlantic Water linked to retreat and disintegration of the 79NG between 10 and 7.5 ka. Extended to even perennial sea ice conditions were predominant on the inner NE Greenland shelf since 7.5 ka. Alfred Wegener Institute Helmholtz Centre ...